Neutrophil to lymphocyte and platelet to lymphocyte ratio in patients with dipper versus non-dipper hypertension. (July 2014) - Sunbul, Murat; Gerin, Fethullah; Durmus, Erdal; Kivrak, Tarik; Sari, Ibrahim; Tigen, Kursat; Cincin, Altug
Abstract Background: Neutrophil to lymphocyte ratio (NLR) and platelet to lymphocyte ratio (PLR) are associated with worse outcome in various diseases. Non-dipping blood pressure pattern is associated with higher cardiovascular mortality. The aim of this study was to explore the association between NLR and PLR in patients with dipper versus non-dipper hypertension. Methods: The study included 166 patients with hypertension. Eighty-three patients (40 male, mean age: 49.1 ± 10.5 years) had dipper hypertension, while 83 patients (41 male, mean age: 52.3 ± 12.7 years) had non-dipper hypertension. Results: Baseline demographic characteristics were similar in both groups. Patients with non-dipper hypertension had significantly higher NLR compared to dipper hypertension (2.3 ± 0.9 versus 1.8 ± 0.5, p < 0.001). Patients with non-dipper hypertension had significantly higher PLR compared to dipper hypertension (117.7 ± 35.2 versus 100.9 ± 30.5, p = 0.001). In univariate analysis, hyperlipidemia, smoking, presence of diabetes, PLR more than 107 and NLR more than 1.89 were among predictors of dipper and non-dipper status. In logistic regression analyses, only hyperlipidemia (odds ratio: 2.96, CI: 1.22–7.13) and PLR more than 107 (odds ratio: 2.62, CI: 1.13–6.06) were independent predictors of dipper and non-dipper status. A PLR of 107 or higher predicted non-dipper status with a sensitivity of 66.3% and specificity of 68.7%. Conclusion: We demonstrated that patients with non-dipper hypertension had significantly higher NLR and PLR compared to dipper hypertension, which has not been reported previously. Moreover PLR more than 107 but not NLR was independent predictor of non-dipper status.